Adolescent cervical disc degeneration in MRI does not predict adult headache or neck pain: A 5-year follow-up of adolescents with and without headache. (August 2014) - Laimi, Katri; Pitkänen, Johanna; Metsähonkala, Liisa; Vahlberg, Tero; Mikkelsson, Marja; Erkintalo, Minna; Aromaa, Minna; Rautava, Päivi; Anttila, Pirjo; Oksanen, Airi; Saltychev, Mikhail; Sillanpää, Matti
Aim: The impact of early degenerative changes of the cervical spine on pain in adulthood is unknown. The objective was to determine whether degeneration in adolescence predicts headache or neck pain in young adulthood. Methods: As part of a follow-up of schoolchildren with and without headache, 17-year-old adolescents with headache at least three times a month ( N  = 47) and adolescents with no headache ( N  = 22) participated in a magnetic resonance imaging (MRI) study of the cervical spine. The same adolescents were re-examined by phone interview at the age of 22 years ( N  = 60/69, 87%). Results: Mild disc degeneration at the age of 17 years was common, but was not associated with either frequent or intensive headache or neck pain at the age of 22 years. Conclusion: Mild degenerative changes of the cervical spine in 17-year-old adolescents cannot be regarded as a cause of future headache or neck pain.